Analisis Kebutuhan Ruang Terbuka Hijau Berdasarkan Kebutuhan Oksigen Menggunakan Teknologi Penginderaan Jauh di Kabupaten Badung - PADMAWATI, ANAK AGUNG PLASA; NUARSA, I WAYAN; SARDIANA, I KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Analysis Of Need For Green Open Space Based On Oxygen Needs Using Remote Sensing Technology In Badung Regency Badung Regency is one of the regencies in Bali Province which has a quite rapid development. Total population of Badung regency in 2018 was 656.90 thousand people with population growth rate of 4.64 % which is the highest growth rate in Bali Province. The objective of this research is (1) to map the percentage of green open space in Badung Regency using Sentinel-2A satellite imagery, (2) to analyze the oxygen needs of Badung regency, and (3) to evaluate the need of green open space in Badung regency based on availability of green open space and the need for oxygen. This study was a descriptive quantitative research who utilize remote sensing technology using the satellite imagery of Sentinel-2A and Gerarkis methods. The methods of sample collection was stratified random sampling with the number of sample is 76. The estimated density of vegetation derived from a comparison between the five indices of vegetation that is NDVI, RVI, DVI, TVI, and SAVI. The result of study shows that the SAVI is the best vegetation index for green open space estimation based on the determination coeffecient (R2) value. The t-test paired confirm as well that there are no significant different between green open space obtaining from estimation using Sentinel-2A satellite imagery and direct measurement on high-scale images. The estimation result of vegetation density indicates that the vast green open space in Badung Regency in 2019 was 22.930,67 ha. The extent of the need of green open space based on oxygen demand by residents, vehicle, and livestock in 2019 is 7.516,34 ha.